RISK CAUSED BY THE SPATIAL FORMATION OF THE CITY OF BURSA (TURKEY) IN HISTORICAL PROCESS, CURRENT DEVELOPMENT PLANS AND LAND USAGES BASED ON DEVELOPMENT PLANS - Kucukali, Ufuk Fatih (European Scientific Journal, ESJ, 2013)
In Turkey, it is observed that there is an overgrowth of population, resolutions on land usage have deteriorating effects on natural ecological balance and consequently environmental problems reached threatening levels for all life forms. It is important to remove the impacts of urbanization, which consume irreplaceable natural resources, through planning methods and techniques. Examination of the current land usage of Bursa Nilüfer Creek Başköy – Kestel Section and its subbasins reveal that location organization was radically changed due to industrialization, and functional areas such as settlements and industrial areas, located on first class agricultural lands and on rock formation with geologically high permeability, create pollutions on the natural resources forming the basin, over acceptable parameters of international standards, as a result of governmental decisions. In this context, resolutions, implementations and their reflections of land usage, population, residence facts and unplanned developments regulated according to development plans prepared in historical perspective and existing development plans in Bursa, the research area, have been discussed within a 20-year process; findings were evaluated and the type and dimension of ecological risks were assessed against international parameters.